HISTORY OF STUDY OF SOMATIC PHRASEOLOGISMS IN GERMAN AND UZBEK LANGUAGES (Multidisciplinary Journal of Science and Technology, 2024)
This scientific article analyzes the level of study of somatic phraseology in German and Uzbek languages, and highlights the work of scientists in this field.